Usability Analysis of The Mobile-Based Cizgi Rent A Car Application Using The WEBUSE Method - Jamilah Karaman (RESEARCH : Journal of Computer, Information System & Technology Management, 2020)
The development of information and communication technology offers convenience for its users.  The use of information and communication technology also has a positive impact on the business world.  For example, the use of advances in information and communication technology in the transportation sector.  Cizqi Rent A Car is a Turkish company that launched a mobile application for online car rental service providers which is expected to make it easier for tourists or local residents who want to rent a car to travel in Turkey.  By conducting usability analysis with the WEBUSE method, this study aims to determine the usability level of the Cizgi Rent A Car application.  From the results of data analysis it is known that this application is quite famous because it has been downloaded by more than 10,000 downloaders from several countries including Indonesia.  This application is used by Indonesians who make work visits and travel to Turkey.  The usability level in the Content, Organization & Readability variables and the Navigation and Links variables can be said to be Good.  The usability level for the User Interface Design variable can be said to be quite bad.  The usability level for the Performance and Effectiveness variables can be said to be moderate.